A novel green synthesis of silver nanoparticles by the residues of Chinese herbal medicine and their biological activities. Issue 3 (5th January 2021) - Wei, Simin; Wang, Yinghui; Tang, Zhishu; Xu, Hongbo; Wang, Zhe; Yang, Tian; Zou, Taiyan
Abstract : A novel method for green synthesis of medicinal AgNPs has been developed by using the residues of Chinese herbal medicine. Abstract : Green synthesis of silver nanoparticles (AgNPs) by using the extracts of Chinese herbal medicines (CHMs) has attracted tremendous attention due to the potential synergistic effect between metal nanoparticles and capping agents. However, since CHMs are precious and expensive, finding other cheap and eco-friendly resources for biosynthesizing AgNPs with superior medicinal activites is necessary. Herbal medicine residues (HMRs) are the by-products of traditional Chinese herbal medicine after decoction and were identified to contain approximately 30–50% of medicinally active ingredients, which may be advantageous for green synthesis of medicinal AgNPs. Inspired by this, we present herein the preparation of AgNPs by reusing Bazheng Mixture residues and evaluate both biosynthesis parameters and bioactivities, where Bazheng Mixture is a famous Chinese patent medicine for relieving inflammation and pain, and allaying fever. The UV-visible spectrum and DLS analysis showed that the as-prepared AgNPs were sensitive to pH, material proportion and incubation time, but the yield was impervious to material proportion. TEM, HRTEM, SAED and DLS characterization found that AgNPs (pH 10.0; material proportion 1 : 1; 6 h) had a face-centered cubic (fcc) structure and spherical shape with an average size of 22.2 ± 0.5 nm covered by anions, and existed in monodispersed form with long term stability. The AgNPs displayed potent toxic effects against both cancer cell lines and pathogens, and superior antioxidant activity. The IC50 for HCT116, HepG2 and HeLa cell lines were 13.07, 19.67, and 26.18 μg mL −1, respectively. The MICs of AgNPs for E. coli and S. aureus were both 50.0 μg mL −1 . The uptake analysis of AgNPs for both pathogens and cancer cell lines was performed to preliminarily illustrate the mechanism of toxic effects. These results confirm that HMRs could be a low-cost, nontoxic and eco-friendly resource for green synthesis of medicinal AgNPs, and also provide an alternative method for general recycling strategies of HMRs.